Women, Men and Sexuality: Gender Studies in Anthropology - ทวีสิทธิ์ สุชาดา (Journal of Social Sciences, Chiang Mai University, 2019)
This article aims primarily to reviewing theoretical and methodological issues in two major academic works concerning cultures of gender and sexuality in Thai society written by Charles F. Keyes. They include Mother or Mistress but Never a Monk: Buddhist Notions of Female Gender in Rural Thailand (1984) and Ambiguous Gender: Male Initiation in a Thai Buddhist Society (1986). The author intends the article to serve as a mark of respect to Prof. Charles F. Keyes. His anthropological contributions, especially which are found in the two selected writings are vital to gender studies both in Thailand and elsewhere. In the two papers Keyes attempted to reinterpret the Thais’ experiences as gendered and sexualized beings against Marxist feminist understanding of gender and sexual cultures in Thai society. He applied both anthropological symbolic/interpretive approach and social constructionist notions of gender and sexuality to investigate the relationship between Thai gender/sexuality systems and Buddhist ideologies. His interpretations were grounded in both texts and contexts drawing from long term engagement with ethnographic fieldwork in Thailand. His writings tried to convince that Thevarada Buddhism was not a gender bias religion and that women and men relations in Thai-Lao and Thai-Yun villages were symbiotic rather than hierarchical.